A heart full of burden - Seshan, Tirunellai Narayana Iyer (New Delhi : UBSPD, 1995)
Collection of addresses chiefly on Indian democratic electoral process and politics delivered by T.N. Seshan, present Chief Election Commissioner of India.
Includes index.
Keywords: Political campaigns -- India; Voting -- India; Elections -- India